The Fatty Acid Composition of Human Follicular Fluid Is Altered by a 6‐Week Dietary Intervention That Includes Marine Omega‐3 Fatty Acids. Issue 2 (12th October 2020) - Kermack, Alexandra J.; Wellstead, Susan J.; Fisk, Helena L.; Cheong, Ying; Houghton, Franchesca D.; Macklon, Nicholas S.; Calder, Philip C.
Abstract: The fatty acid composition of human follicular fluid is important for oocyte development and for pregnancy following in vitro fertilization (IVF). This study investigated whether a dietary intervention that included an increase in marine omega‐3 fatty acids, olive oil and vitamin D alters the fatty acid composition of human follicular fluid. The association of lifestyle factors with follicular fluid fatty acid composition was also investigated. Fifty‐five couples awaiting IVF were randomized to receive the 6‐week treatment intervention of olive oil for cooking, an olive oil‐based spread, and a daily supplement drink enriched with vitamin D and the marine omega‐3 fatty acids docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) and 56 couples were randomized to receive placebo equivalents. Dietary questionnaires were completed, and samples of blood were taken before and after the intervention. Follicular fluid was collected at oocyte retrieval and the fatty acid profile assessed using gas chromatography. In the control group, individual fatty acids in red blood cells and follicular fluid were significantly correlated. Furthermore, a healthier diet was associated with a lower percentage of follicular fluid arachidonic acid. The follicular fluid of women in the treatment group contained significantly higher amounts of EPA and DHA compared to the control group, while the omega‐6 fatty acids linoleic, γ‐linolenic, dihomo‐γ‐linolenic, and arachidonic were lower. This is the first report of a dietary intervention altering the fatty acid composition of follicular fluid in humans. Further research is required to determine whether this intervention improves oocyte quality.